H/ACA Box Small Nucleolar RNA 7A Promotes the Self‐Renewal of Human Umbilical Cord Mesenchymal Stem Cells. (24th November 2016) - Zhang, Yan; Xu, Chen; Gu, Daolan; Wu, Minjuan; Yan, Binghao; Xu, Zhenyu; Wang, Yue; Liu, Houqi
Abstract: Human umbilical cord blood derived mesenchymal stem cells (uMSC) are pluripotent cells that have been now considered as a promising candidate for various cell‐based therapies. However, their limited in vitro proliferation ability and the gradual loss of pluripotency set barricades for further usages. Emerging evidence suggests that small nucleolar RNAs (snoRNA) are actively involved in cell proliferation especially in tumor cells, but their roles in stem cells are largely unknown. In this study, we demonstrated that H/ACA box small nucleolar RNA 7A (SNORA7A) is inversely correlated to the decreased proliferation rate during in vitro passaging of uMSC. Further investigations indicate that SNORA7A overexpression can promote uMSC proliferation and self‐renewal. The inhibition of SNORA7A using antisense oligonucleotides significantly reduces the expression and the binding of SNORA7A to DKC1, core protein that essential to form small nucleolar ribonucleo‐particles (snoRNP) complex and catalyze pseudouridines in 28S RNA. And the inhibition also significantly suppresses uMSC proliferation and self‐renewal. Moreover, overexpression of SNORA7A transcripts with mutations of binding regions for snoRNP core proteins and 28S RNA did not induce proliferation and self‐renewal. Besides, SNORA7A also suppresses both the osteogenic and adipogenic differentiation, strengthening its self‐renewal maintaining roles in uMSC. Taken together, our study for the first time showed that H/ACA box snoRNAs are actively involved in MSC proliferation as well as pluripotency control, and we identify SNORA7A as one of the critical snoRNAs that regulate the proliferation and self‐renewal of uMSC through snoRNP recruiting. Stem Cells 2017;35:222–235